Thymus size and its changes during treatment of children with severe acute malnutrition - Selvaraj, Stalin; Venkatasamy, Seenivasan; Sinnathambi, Sathyaseelan (International Journal of Contemporary Pediatrics, 2020)
Background: The study was conducted to radiologically demonstrate increase in thymus size with clinical recovery following nutritional rehabilitation in children with severe acute Malnutrition and to correlate the improvement with anthropometric and biochemical parameters. Methods: Prospective observational study was conducted in 60 children in the age group of 6months to 24 months with severe acute malnutrition. Children with severe systemic illnesses were excluded from study. After obtaining informed consent from parents, history focusing on demography, perinatal events, nutrition including breast feeding and immunization status were recorded. Anthropometric parameters were measured. All relevant blood investigations and ultra-sonogram of the chest for thymus size were done. All children were followed up during the course of hospital stay till discharge and were also followed up after 2 months. Relevant blood investigations and ultrasonogram of chest for thymus size were also done during follow up. Results: The difference in means of thymic area by imaging at admission and at discharge (p and lt;0.0001) and at admission and after 8 weeks (p and lt;0.0001) were statistically significant. The increase in weight, length, weight for length, mid upper arm circumference, hemoglobin, total protein, serum albumin, serum globulin from admission to discharge and from discharge to 8 weeks after admission was statistically significant. Conclusions: Thymus size can be used as a marker of immunological dysfunction in severe acute malnutrition and as a marker of severity of the illness. The thymus size was found to be increasing in size during nutritionally rehabilitation and recovery from the illness. Correlations between anthropometric parameters and thymic size are not robust in under-nourished state and during nutritional rehabilitation.